If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)(7x + 10) = 0 Reorder the terms: (6 + x)(7x + 10) = 0 Reorder the terms: (6 + x)(10 + 7x) = 0 Multiply (6 + x) * (10 + 7x) (6(10 + 7x) + x(10 + 7x)) = 0 ((10 * 6 + 7x * 6) + x(10 + 7x)) = 0 ((60 + 42x) + x(10 + 7x)) = 0 (60 + 42x + (10 * x + 7x * x)) = 0 (60 + 42x + (10x + 7x2)) = 0 Combine like terms: 42x + 10x = 52x (60 + 52x + 7x2) = 0 Solving 60 + 52x + 7x2 = 0 Solving for variable 'x'. Factor a trinomial. (6 + x)(10 + 7x) = 0Subproblem 1
Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6Subproblem 2
Set the factor '(10 + 7x)' equal to zero and attempt to solve: Simplifying 10 + 7x = 0 Solving 10 + 7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 7x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 7x = 0 + -10 7x = 0 + -10 Combine like terms: 0 + -10 = -10 7x = -10 Divide each side by '7'. x = -1.428571429 Simplifying x = -1.428571429Solution
x = {-6, -1.428571429}
| 3y^2-8y=2 | | 6-10a=8-9a | | 8-4x=18-5x | | 8b^2-5b=10 | | 4x+23-10=34 | | (3,2),(4,1)= | | p=x^2-4x-8 | | 2x^2+15x+18=0 | | 4a+10c=1 | | x^6-8y^3=0 | | 3(2x-6)-[(x-(3x-8)+2)-1]=2-(3-2x) | | 3v+48=9v | | 5x-3(7+x)=29 | | 3x+7=x+2 | | 6(3b+6)=2(6b-22) | | A=1/2(6+3)3 | | 8a-2b=11 | | 5(2x-1)+3x=2(x+5) | | A=1/2(6+3) | | x^2+4x^2-25=2x^2 | | y=2x^2-8x-4 | | A=1/2(4+3)2 | | d+(2d-3)=13(d-1) | | A=1/2(10+7)4 | | 4.9q-5.1-5.3q=-1.4q-4.8 | | -45m+68=84m | | 9x+6=7+18 | | 6x+5x+4+9=8x+4+2x | | 3n+2(n+4)=56 | | 111=79 | | 5.7q-1.3-5.6q=0.9q-3.4 | | -54-8v=-7v+21 |